Willingness to pay for certification and labeling of chicken meat in the Mymensingh District of Bangladesh. - Mishu, Mahbuba Akther; Saha, Sourav Mohan; Prodhan, Md Masudul Haque; Rahman, Md Mostafijur; Khan, Md Akhtaruzzaman (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study explores consumers’ willingness to pay (WTP) for labeled and certified chicken meat in Mymensingh district, examining the key socioeconomic and demographic factors that shape these preferences. Materials and Method: Data were gathered through structured interviews with 300 participants from diverse urban and rural demographics, encompassing various occupational groups. The analysis employed logistic regression models to examine the determinants of WTP for labeling and certification, with a focus on variables such as income, education, health perception, environmental awareness, dependency ratio, and market distance. Results: The study found that a significant proportion of consumers preferred labeled (64%) and certified (71%) broiler meat. Strong links between higher income and education levels and increased WTP suggest that wealthier and more literate consumers are more likely to invest in food safety measures. Positive health and environmental perceptions also played a role, with more conscious consumers willing to pay a premium for labeled and certified products. On the other hand, a higher dependency ratio and greater market distance were associated with lower WTP, underscoring the impact of socioeconomic constraints and accessibility issues on consumer choices. Conclusion: Introducing labeling and certification systems could strengthen consumer trust and enhance public health, offering substantial benefits to both the poultry industry and the broader economy in Bangladesh. J. Adv. Vet. 11(3): 772-781, September 2024 http://doi.org/10.5455/javar.2024.k829